1980
DOI: 10.1002/apmc.1980.050920104
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and properties of some alkenyl‐ and alkinyl‐2‐cyanoacrylates

Abstract: Some alkenyl-and alkinyl-2-cyanoacrylate monomers, possessing adhesive properties were synthesized. The ease of esterification of cyanoacetic acid, the first step of the synthesis, with some alcohols was in the following order:CH,CH, Die Einfuhrung von Doppel-und Dreifachbindungen erhohte die Festigkeit. Ungesattigte Cyanacrylate zeigten eine bessere Temperaturbestandigkeit der Klebstoffverbindung: CH, = CHCH,-> CH = CCH2-> CH = CC(CH,)H-> CH = CC(C,H,)H-> Alkyl. Dies wurde durch die Bildung einer Vernetzung i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1982
1982
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…For example, Denchev et al report difficulties in depolymerizing oilgo‐allyloxyethyl cyanoacrylate even when it is heated to temperatures in excess of 300 °C 1. Similarly, Kotzev et al were unable to isolate the following cyanoacrylate monomers: 2‐methyl‐2‐propenyl, 2‐butenyl and 1‐propyl‐2‐propenyl83 and Vijayalakshmi et al report difficulties in obtaining tert ‐butyl and undecyl cyanoacrylate 38. Using a molar excess of the cyanoacetate in the condensation step, Denchev et al were able to obtain a more easily depolymerizable product, but the yields were still comparatively low 1…”
Section: Resultsmentioning
confidence: 99%
“…For example, Denchev et al report difficulties in depolymerizing oilgo‐allyloxyethyl cyanoacrylate even when it is heated to temperatures in excess of 300 °C 1. Similarly, Kotzev et al were unable to isolate the following cyanoacrylate monomers: 2‐methyl‐2‐propenyl, 2‐butenyl and 1‐propyl‐2‐propenyl83 and Vijayalakshmi et al report difficulties in obtaining tert ‐butyl and undecyl cyanoacrylate 38. Using a molar excess of the cyanoacetate in the condensation step, Denchev et al were able to obtain a more easily depolymerizable product, but the yields were still comparatively low 1…”
Section: Resultsmentioning
confidence: 99%
“…Monomers incorporating cyanoacrylate groups or with an ally! and a cyanoacryl ate group in the molecule have been synthesized [35,36]. These compounds polymerize anionically and crosslink when heated or when exposed to certain polymerization initiators.…”
Section: Development Of Adhesive Bonding Techniquesmentioning
confidence: 99%
“…shown that interfaces cemented with ally 1 cyanoacrylate have improved heat stability compared to less cross-linked cyanoacrylate joints [36]. Formulations incorporating allyl cyanoacrylates and higher alkyl 2-cyanoacryl ates difunctional aromatic diol dimethacrylate esters as well as tri(allyloxy)-s-triazine and peroxide free radical initiators have been suggested…”
Section: Recent Studies Havementioning
confidence: 99%
“…Therefore, the exploration of water-usage chemistry is an important issue to achieve sustainable technologies . Water is already being used as a chemical trigger to induce transformations in materials such as cements and cyanoacrylates, which harden after mixing or with contact with water to form robust structures. However, other fundamental chemistry methods for such water-usage technologies are still quite limited, and there exist considerable areas for development.…”
mentioning
confidence: 99%